2020
DOI: 10.3390/agriculture11010020
|View full text |Cite
|
Sign up to set email alerts
|

Planimetric Determination of the Static Space of Cull Sows as the First Step towards a Recommendation of Loading Densities for Cull Sows during Road Transportation in the European Union

Abstract: The available floor space is an important welfare factor for cull sows during transportation. Sows of modern genetics reach a size and weight far exceeding those of fattening pigs. In most countries, there are no binding, consistent regulations for the maximum loading densities, especially for sows during road transportation. As a first step towards such recommendations, the physical floor space requirement (static space) of 100 sows of a current breed, while standing and lying down, were determined using cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Curtis et al (1989) estimated that in order to get up and lie down comfortably, a sow weighing 300 kg uses 220 cm in length and 86 cm in width. Thus, a stall measuring less than 220 × 86 cm will impede natural lying down and getting up behaviour (Arndt et al, 2020).…”
Section: Resting Problems and Related Abmsmentioning
confidence: 99%
“…Curtis et al (1989) estimated that in order to get up and lie down comfortably, a sow weighing 300 kg uses 220 cm in length and 86 cm in width. Thus, a stall measuring less than 220 × 86 cm will impede natural lying down and getting up behaviour (Arndt et al, 2020).…”
Section: Resting Problems and Related Abmsmentioning
confidence: 99%
“…However, comparing sow dimensions for length, width and height between that calculated by the allometric equations proposed by Petherick and Philips (2009) to the measurements taken by Moustsen et al (2011), in Danish sows ranging from parity 1 to 7, indicates that the allometric equations continue to provide close estimations of the body dimensions of these modern genetics. Planimetric analysis of the static space floor area occupied by sows in different postures (average sow weight 235 kg, min: 187; max: 310 kg) has identified that when standing, the occupied floor area ranges from 0.42 m 2 to 0.47 m 2 (min: 0.34; max: 0.59 m 2 ), and sternal lying requires an average floor space of 0.63 m 2 (min: 0.52; max: 0.71 m 2 ), (Arndt et al, 2020). This is lower than the minimum space allowance estimated for sows to stand and lie sternally as calculated with a k-value of 0.019.…”
Section: B) Horizontal Space I) Space To Accommodate Physical Sizementioning
confidence: 99%
“…Planimetric analysis of the static space floor area occupied by sows in different postures (average sow weight 235 kg, min: 187; max: 310 kg) has identified that when standing, the occupied floor area ranges from 0.42 m 2 to 0.47 m 2 (min: 0.34; max: 0.59 m 2 ), and sternal lying requires an average floor space of 0.63 m 2 (min: 0.52; max: 0.71 m 2 ), (Arndt et al., 2020). This is lower than the minimum space allowance estimated for sows to stand and lie sternally as calculated with a k‐value of 0.019.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation